Credit securitization decisions - Sarmiento, Camilo (Routledge Taylor and Francis Group, 2012)
Government Sponsor Enterprises (GSEs) purchase mor tgage loans from approved lenders, either for cash or in exchange for a mortgage-backed security that comprises thoseloans.TheGSEs guarantee timelypayment ofinter est and principal. The mortgage seller may then hold that security or sell it. A fundamental component of loan securitization decisions is the economic environment. To balance capital requirements and manage credit risk, lenders slice and dice mortgages for securitization versus holding unsecured loans for investment in their portfolios. This article estimates factors that explain credit securitization decisions with GSEs. Using secur itization data from 2005 to 2009, we show the impact that House Price (HP) trends have on decisions of banks to securitize new originations with GSEs. For the analysis, we also measure the preferences of banks to securitize certain loan products as well as the role of note rate spreads on credit securitization decisions.

Las Empresas Patrocinadoras del Gobierno (GSE) compran préstamos hipotecarios de prestamistas aprobados, ya sea en efectivo o a cambio de un título respaldado por hipotecas que comprende esos préstamos. Las GSE garantizan el pago oportuno de los intereses y el principal. El vendedor de la hipoteca puede entonces conservar ese valor o venderlo. Un componente fundamental de las decisiones de titulización de préstamos es el entorno económico. Para equilibrar los requisitos de capital y gestionar el riesgo crediticio, los prestamistas dividen las hipotecas para su titulización en lugar de mantener préstamos no garantizados para invertir en sus carteras. Este artículo estima los factores que explican las decisiones de titulización de créditos con GSE. Utilizando datos de titulización de 2005 a 2009, mostramos el impacto que tienen las tendencias del precio de la vivienda (HP) en las decisiones de los bancos de titularizar nuevas originaciones con GSE. Para el análisis, también medimos las preferencias de los bancos para titulizar ciertos productos crediticios, así como el papel de los diferenciales de tasas de interés en las decisiones de titulización de crédito.
Keywords: Titulización; Securitización; Préstamos bancarios; Créditos bancarios; Bank loans; Bank credits; securitization; GSE; portfolio; risk